2010
DOI: 10.1017/s002211200999423x
|View full text |Cite
|
Sign up to set email alerts
|

Channel flow over large cube roughness: a direct numerical simulation study

Abstract: Computations of channel flow with rough walls comprising staggered arrays of cubes having various plan area densities are presented and discussed. The cube height h is 12.5 % of the channel half-depth and Reynolds numbers (u τ h/ν) are typically around 700 -well into the fully rough regime. A direct numerical simulation technique, using an immersed boundary method for the obstacles, was employed with typically 35 million cells. It is shown that the surface drag is predominantly form drag, which is greatest at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
175
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 216 publications
(210 citation statements)
references
References 40 publications
31
175
3
1
Order By: Relevance
“…The roughness length results, in figure 8(a), closely follow the skin friction trends as a function of both the solidities, as shown in table 1. The drag-peak location herein is partially in contrast with previous studies, for which it was found at λ P ≡ λ F ≈ 0.15 (Hagishima et al 2009;Leonardi & Castro 2010;Kanda et al 2004) and λ P ≡ λ F ≈ 0.16 (Santiago et al 2008;Coceal & Belcher 2004). These differences are perhaps not surprising giving the high uncertainty in the fitting procedure which results in the visible scatter of the data for different studies in figure 8(a), even when values of similar frontal and plan solidity are considered.…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterscontrasting
confidence: 99%
See 3 more Smart Citations
“…The roughness length results, in figure 8(a), closely follow the skin friction trends as a function of both the solidities, as shown in table 1. The drag-peak location herein is partially in contrast with previous studies, for which it was found at λ P ≡ λ F ≈ 0.15 (Hagishima et al 2009;Leonardi & Castro 2010;Kanda et al 2004) and λ P ≡ λ F ≈ 0.16 (Santiago et al 2008;Coceal & Belcher 2004). These differences are perhaps not surprising giving the high uncertainty in the fitting procedure which results in the visible scatter of the data for different studies in figure 8(a), even when values of similar frontal and plan solidity are considered.…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterscontrasting
confidence: 99%
“…It is clearly visible in figure 9(b) that the virtual origin increases with an increase in plan solidity till it approaches its asymptote at d = h. The latter is qualitatively consistent with previous studies which have shown that the zero plane displacement tends to assume larger values (i.e. d tends to h) as the plan solidity increases (Kanda et al 2004;Hagishima et al 2009;Leonardi & Castro 2010). This trend is also consistent with the predictions from Macdonald (1998).…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…The constants a i estimated in this way for Łódź are close to those given by Kaimal et al (1972) Oncley et al 1996;Frenzen and Vogel 2001;Andreas et al 2006;Li et al 2008;Leonardi and Castro 2010;Kanda et al 2013) suggest that κ could be lower than 0.4, especially over rough surfaces (κ decreases with increasing roughness Reynolds number). The Kolmogorov constant, α u , also ranges from 0.36 to 0.56 (Högström 1990), which introduces additional imprecision in the estimation of φ ε (0).…”
Section: The Spectra Of Velocity Componentssupporting
confidence: 77%